2011
DOI: 10.1504/ijtmkt.2011.043811
|View full text |Cite
|
Sign up to set email alerts
|

A model of brand switching by lead users of high-tech capital equipment

Abstract: This study investigates the antecedents of brand switching by lead users of high-tech capital equipment. In markets for capital equipment, the incumbent is usually assumed to have an advantage because of high switching costs. However, much of the research on brand switching focuses on mass-market consumers of competitive products, where switching barriers are manageable. A model of the factors behind brand switching for capital equipment is developed and tested with data gathered by a survey of research centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…If consumers have a favorable attitude toward switching their smartphone, their intentions to switch do not increase if they do not have the financial resources or ability to do so (Bansal and Taylor 2002). On the other hand, H5e confirms that the greater the financial switching costs, the lower the consumers' switching intentions to "the other smartphone", a finding consistent with results of previous studies (Al- Kwifi and McNaughton, 2011). Financial switching costs are consistently found to be the main switching barrier perceived by consumers (Bansal and Taylor, 2002).…”
Section: Discussionsupporting
confidence: 84%
“…If consumers have a favorable attitude toward switching their smartphone, their intentions to switch do not increase if they do not have the financial resources or ability to do so (Bansal and Taylor 2002). On the other hand, H5e confirms that the greater the financial switching costs, the lower the consumers' switching intentions to "the other smartphone", a finding consistent with results of previous studies (Al- Kwifi and McNaughton, 2011). Financial switching costs are consistently found to be the main switching barrier perceived by consumers (Bansal and Taylor, 2002).…”
Section: Discussionsupporting
confidence: 84%
“…Product features and their performance are considered the most important aspects in building a user's competitive advantage (Al-kwifi and McNaughton, 2011). And given that high-technology markets, such as that for medical imaging devices, are constantly changing, users are continuously evaluating the features and performance of their existing products and assessing whether other products with wider features and performance are able to improve their market position and help them gain a competitive advantage (Al-kwifi and McNaughton, 2013).…”
Section: Product Featuresmentioning
confidence: 99%
“…They define high-technology capital product as "a technology-based product that is acquired infrequently, significantly exceeds the cost of an average purchase in a customer's organization, and has an extended and complex purchasing process". Al-kwifi and McNaughton (2011) found that lead users are willing to face strong barriers to switching to a new technology that is critical to the renewal of organizational capabilities. They state that the decision to switch among high-technology capital product is influenced mainly by the product design, which usually contains specific capabilities that are important to achieve a competitive advantage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…John, Weiss, and Dutta (1999) explained that the feature of a product is a significant factor to increase the user's interest to switch brands. An interesting feature is an advantage in the competition (Al-Kwifi & McNaughton, 2011) and able to make smartphone users switch brand. In this study, we conclude that the more attractive the promotion is made it will make customers lose their interest to switch to other brands.…”
Section: Relationship Between Trust and Brand Switchingmentioning
confidence: 99%